(untitled) (ResearchJet Journal of Analysis and Inventions, 2021)
In recent years, the study of folklore samples developed by individual artists has developed significantly. After all, the national values of the people, the national identity, go back to the roots of folklore, formed over the centuries, passing through a series of times. Gaffor Muminov, a folklorist, says: “It must be acknowledged that folk art has had a direct and indirect effect on the mind of a true artist throughout his life.